The effect of seed provenance and organic fertilizer types on growth and yield of G2 potato (Solanum tuberosum L. cv. Medians) seeds in Jatinangor medium plains - Rafiif, Mohammad Faisal; Sutari, Wawan; Hamdani, Jajang Sauman (Universitas Padjadjaran, 2024)
Potato growth is influenced by seed provenance and fertilization, but the availability of high-quality potato seeds is still limited. To overcome those challenges, solutions include using temperature-tolerant potato varieties from medium plains and applying organic fertilizers to improve potato growth and yield. The purpose of this research was to determine the effect of the interaction between seed provenance and application of organic fertilizers on the growth and yield of G2 potato seeds of the Medians cultivar in the Jatinangor medium plains. The research was conducted from June to October 2023 at the Ciparanje Experimental Farm, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The research design used was a Factorial Randomized Group Design (RBD). The first factor is the provenance of the potato seeds from the medium and high plains. The second factor is the type of organic fertilizer, namely chicken manure, cow manure, and guano fertilizer. The results showed that there was no interaction between the seed provenance and types of organic fertilizer on the growth and yield of G2 potato seeds of the Medians cultivar in Jatinangor medium plains. The use of seeds from medium plains had a significant effect on plant height, plant dry weight, and the percentage of stolons forming tubers. The application of cow manures with a dose of 225 g gave the best effect on leaf area, the number of tubers, and the weight of tubers per plant.